Pembangunan ibu kota nusantara (ikn): antara peluang strategis dan tantangan transformasi nasional - Daroini, Maiya Hasanatud - (Maliki Interdisciplinary Journal, 2025)
The relocation of the national capital from Jakarta to Nusantara Capital City (IKN) in East Kalimantan represents a strategic national policy with multidimensional impacts, encompassing political, economic, social, cultural, and environmental aspects. This policy not only reflects the intention to ease the burden on Jakarta but also serves as a manifestation of equitable development and Indonesia’s transformation toward becoming an advanced and sustainable nation. Through a normative approach and literature review, this article highlights legal principles, governmental adages, regional development theories, and policy insights from other countries that have undertaken similar initiatives. The findings indicate that the development of IKN holds strategic potential to become a catalyst for national development, yet it must be accompanied by holistic planning and inclusive public participation.